Electrochemical Supercapacitors for Energy Storage and Delivery : Fundamentals and applications - Yu, Aiping; Chabot, Victor; Zhang, Jiujun (Taylor & Francis, 2013)
Although recognized as an important component of all energy storage and conversion technologies, electrochemical supercapacitators (ES) still face development challenges in order to reach their full potential. A thorough examination of development in the technology during the past decade, Electrochemical Supercapacitors for Energy Storage and Delivery: Fundamentals and Applications provides a comprehensive introduction to the ES from technical and practical aspects and crystallization of the technology, detailing the basics of ES as well as its components and characterization techniques. The book illuminates the practical aspects of understanding and applying the technology within the industry and provides sufficient technical detail of newer materials being developed by experts in the field which may surface in the future. The book discusses the technical challenges and the practical limitations and their associated parameters in ES technology. It also covers the structure and options for device packaging and materials choices such as electrode materials, electrolyte, current collector, and sealants based on comparison of available data. Supplying an in depth understanding of the components, design, and characterization of electrochemical supercapacitors, the book has wide-ranging appeal to industry experts and those new to the field. It can be used as a reference to apply to current work and a resource to foster ideas for new devices that will further the technology as it becomes a larger part of main stream energy storage.
English
Keywords: Industrial chemistry; Energy; Electrical engineering; Materials science; Applications; Apps; Deliv; Delivery; Electro; Electrochemical